'I need to be strong and competent': a narrative inquiry of a student-teacher's emotions and identities in teaching practicum. Issue 7 (2nd October 2016) - Yuan, Rui; Lee, Icy
Abstract: In teacher identity research, limited attention has been paid to how pre-service teachers constructed their identities by negotiating with different emotions in their practice. To fill this gap, the present study, drawing upon the approach of narrative inquiry, explores how a student-teacher – Ming – negotiated and navigated conflicting emotions in the process of becoming a teacher. The findings show that while Ming experienced some negative feelings in his work, which challenged his self-belief as a teacher, the positive emotions derived from his students' progress and recognition contributed to his teacher identity. However, due to the constraints imposed by his mentor and the school context, his negative emotions gradually escalated, posing severe impediments to his teacher identity. The emotional flux and identity change of the student-teacher can be attributed to his professional learning in the structural and cultural working conditions with hidden 'emotional rules' embedded in the practicum school. This paper argues for the inclusion of teacher emotions as an indispensable part of pre-service teacher education.